CHEMICAL COMPOSITION OF BACTERIA - Bakayeva Shoira Baxshilloyevna; Asadova Ruxsora Avazovna; Achilova Azimabonu Akmalovna (Western European Studies, 2025)
In this article,the chemical composition of bacteria, i.e. the proteins, carbohydrates,lipids, and nucleic acids that make up their composition, is studied,and what their role in the bacterial cells is explaind.In addition, elements such as nitrogen, carbon, oxygen, and hydrogen are also found in the bacterial cell.Water and enzymes can also be found in the bacterial cell
Keywords: Chemical composition of the bacterial cell; water; dry matter